STING pathways and Sjögren’s syndrome: Exploration from mechanism to treatment - Ka, Yuxiu; Tan, Tingting; Fan, Yihua; Liu, Wei; Wang, Aihua; Wang, Wen; Yuzhen, Gesang; Zhang, JingYi; Yao, Xiaoge; Lin, Xueying; Wu, Yuanhao (Frontiers in Immunology, 2025)
Sjögren’s syndrome (SS) is an autoimmune disease characterized by abnormal lymphocyte proliferation and progressive exocrine gland dysfunction. The Stimulator of Interferon Genes (STING) pathways, as an important intracellular immune hub, overactivation can drive abnormally high expression of type I interferon and induce inflammatory cell infiltration, which is considered an important mechanism in the pathogenesis of SS. However, currently there is limited clinical evidence for direct activation of STING in human SS, and its tissue-specific regulatory mechanisms in target organs also need to be further elucidated. Based on this, STING pathway inhibitors have shown potential value in treating SS. This article systematically reviews the molecular mechanisms of the STING pathways in the pathogenesis of SS, explores its feasibility as a therapeutic target, and provides new evidence and ideas for precision treatment of SS.